MENINGKATKAN KETERAMPILAN APLIKASI AKUNTANSI MYOB PADA SISWA SMK AL-IRSYAD KOTA TEGAL - Hetika Hetika; Fitri Amaliyah; Krisdiyawati Krisdiyawati; Anita Karunia (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
Accounting information is one of the basis for making economic and business financial decisions. The importance of accounting information as a basis for decision making is increasingly recognized by business actors. Accounting information is generated by a process known as the accounting cycle. Along with the development of technology, the accounting cycle carried out by companies is mostly computer-based. Therefore, the ability in the field of computers is a necessity and even a demand for professionals, especially professionals in the accounting field. Students majoring in accounting are prospective professionals in the accounting field. Therefore, students majoring in accounting need to be equipped with computer skills in accounting. MYOB accounting computer application is an application designed to assist in the preparation of financial statements. MYOB accounting computer application is one of the skills that must be possessed by Vocational High School (SMK) students majoring in accounting. Currently, the Uji Kompetensi Keahlian (UKK) and Lomba Kompetensi Siswa (LKS) use the MYOB accounting application as one of the test subjects. The problems faced by schools are related to the limited ability of students to operate accounting computers, especially MYOB and the school's concerns regarding the inability of students to solve UKK and LKS questions for MYOB accounting applications. Therefore, the community service team provides MYOB accounting application training. This activity is carried out in three stages. The first stage of the activity team discusses with partners related to the problems that occur. The second stage, the activity team determines the theme of the activity and prepares the material for the activity. The third stage, the activity team conducts an evaluation. The results of the activity showed that there was an increase in the ability of participants in compiling reports of pleasure using the MYOB accounting application.Â